Crustal structure of South India from aeromagnetic data - Rajaram, M.; Anand, S.P. (My University, 2003)
Degree sheet Aeromagnetic maps over Peninsular India (8 to 180 degrees N) purchased from the Geological Survey of India are machine digitized along contours, corrected for the main field, re-gridded at 2 km interval, continued to a common altitude of 5000 feet and merged to generate an accurate crustal anomaly map of the region. These are further analysed quantitatively to decipher the crustal structure of the region. The analytic signal map of the aeromagnetic data delineates the main magnetic sources in the region; these are mainly related to the mapped charnockites within the Southern Granulite Terrain (SGT) and the mapped iron ore bodies and intrusives in the Dharwar region. It helps redefine the Geology of the region in inaccessible areas. The Euler deconvolution gives the location, depth and nature of the sources. It reflects the extent of exhumatiom of the charnockites in the region. A 2D profile analysis of the aeromagnetic data along the existing DSS profile suggests that a simple model assuming the charnockites as the country rock is able to reproduce the anomalies.
Keywords: Tectonics; Euler; Aeromagnetic data; Crustal structure; South India; Aeromagnetic maps